Primary Immunodeficiency Diseases: A Patient-Oriented Problem-Solving (POPS) Exercise - Kelly Jackson; Patricia Lally; William Blue (Association of American Medical Colleges, 2010)
Abstract Introduction This exercise on primary immunodeficiency diseases is designed as a small-group discussion module to be used for first- or second-year medical students. The primary goal is to introduce major concepts of primary immune deficiency in a clinical case-based setting. Methods Students should complete a pretest and preliminary reading, then attend a small-group discussion session lasting approximately 2 hours. This resource includes supplemental material containing growth charts, clues to diagnosing primary immune deficiency, posttest, and posttest answers. However, faculty are free to modify the exercise to fit the needs of their own course or institution. Results A pilot run of this exercise was done with three groups of four second-year students in August 2009. Seventy-three percent recommended use of the exercise, 73% said the exercise achieved its objectives, and 100% said the primary immunodeficiency diseases increased their understanding of immunodeficiency. Additionally, instructions were clarified based upon the student feedback. Discussion The table of potential laboratory tests in section three may cause students to spend too much time and get bogged down as they try to approach the case as real physicians. We plan to limit their time working on this table so that the emphasis remains on the immunologic concepts.